Robust Flood Risk Management Strategies Through Bayesian Estimation and Multi-objective Optimization - Sobhaniyeh, Zahra; Niksokhan, Mohammad Hossein; Omidvar, Babak; Gaskin, Susan (International Journal of Environmental Research, 2021)
Management and control of flood hazards, the most frequent natural disaster worldwide, has become a greater challenge due to the increasingly unpredictable precipitation and runoff due to climate change. As many rural areas in Iran are vulnerable to flash floods occurring mainly in the spring, more accurate plans are needed to help reduce the risk of related damage. To address this concern, a robust methodology using multi-objective optimization is proposed, which incorporates the large uncertainties in the modeling parameters defining the risk of flooding. The proposed framework has been implemented in the upper catchment of the Taleghanrood river in the Taleghan district in Iran, which is vulnerable to flooding. The results provide a detailed performance assessment of alternative infrastructure designs, which will help to increase the efficiency of flood management strategies. The optimization uses multi-criteria optimization evolutionary algorithms (MOEA) and Bayesian estimation concepts. The resulting specific design plans, as levees’ height increases over a 50-year time horizon, for controlling floods under given scenarios reflect the uncertainty in the parameters.

A Global Flood Risk Modeling Framework Built With Climate Models and Machine Learning - Carozza, David A.; Boudreault, Mathieu (Journal of Advances in Modeling Earth Systems, 2021)
AbstractLarge scale flood risk analyses are fundamental to many applications requiring national or international overviews of flood risk. While large‐scale climate patterns such as teleconnections and climate change become important at this scale, it remains a challenge to represent the local hydrological cycle over various watersheds in a manner that is physically consistent with climate. As a result, global models tend to suffer from a lack of available scenarios and flexibility that are key for planners, relief organizations, regulators, and the financial services industry to analyze the socioeconomic, demographic, and climatic factors affecting exposure. Here we introduce a data‐driven, global, fast, flexible, and climate‐consistent flood risk modeling framework for applications that do not necessarily require high‐resolution flood mapping. We use statistical and machine learning methods to examine the relationship between historical flood occurrence and impact from the Dartmouth Flood Observatory (1985–2017), and climatic, watershed, and socioeconomic factors for 4,734 HydroSHEDS watersheds globally. Using bias‐corrected output from the NCAR CESM Large Ensemble (1980–2020), and the fitted statistical relationships, we simulate 1 million years of events worldwide along with the population displaced in each event. We discuss potential applications of the model and present global flood hazard and risk maps. The main value of this global flood model lies in its ability to quickly simulate realistic flood events at a resolution that is useful for large‐scale socioeconomic and financial planning, yet we expect it to be useful to climate and natural hazard scientists who are interested in socioeconomic impacts of climate.
Publisher: American Geophysical Union (AGU)

Données d’utilisation d’un autotraitement guidé en ligne pour promouvoir la résilience après une catastrophe naturelle - Lebel, Jessica; Flores-Tremblay, Thalie; Binet, Émilie; Ouellet, Marie-Christine; Belleville, Geneviève (Santé mentale au Québec, 2021)
Objectifs Malgré l’existence de plusieurs traitements en ligne pour les personnes avec un trouble de stress posttraumatique (TSPT), peu d’études se sont penchées sur les données d’utilisation d’une telle intervention. Étant donné le potentiel de la modalité en ligne à pallier les obstacles limitant l’accès à l’aide psychologique, il importe de documenter les interactions des usagers avec ces outils en lien avec l’amélioration des symptômes ciblés. L’objectif de cette étude est de documenter les données d’utilisation de la plateforme de traitement en ligne RESILIENT par les personnes évacuées des feux de Fort McMurray, Alberta (Canada), et d’examiner leur association avec l’efficacité du traitement sur les symptômes de trouble de stress posttraumatique (TSPT), d’insomnie et de dépression, et l’adhésion au traitement, mesurée par le nombre de modules consultés par les participants. Méthode Quatre-vingt-dix-sept personnes évacuées des feux de Fort McMurray présentant des symptômes de TSPT, d’insomnie et de dépression sont incluses dans la présente étude. Les participants étaient invités à utiliser la plateforme RESILIENT, un autotraitement en ligne guidé par un thérapeute qui cible les symptômes de TSPT, le sommeil et l’humeur, et comprend 12 modules offrant des stratégies de thérapies cognitives et comportementales (TCC) basées sur les données probantes. Des données d’utilisation objectives (p. ex. nombre de modules consultés) et subjectives (p. ex. niveau d’efforts investis) ont été recueillies. Résultats Afin de prédire la réduction des symptômes de TSPT, de dépression et d’insomnie, ainsi que le nombre de modules consultés par les participants, des modèles de régressions séquentielles ont été effectués, avec un contrôle statistique pour les symptômes prétraitement, l’âge et le genre. Les modèles finaux ont révélé qu’une réduction des symptômes de TSPT, de dépression et d’insomnie était prédite significativement par le nombre de modules consultés (β = - 0,41 ; - 0,53 ; - 0,49 respectivement, tous p < 0,001) ainsi que par le niveau d’efforts moyen autorapporté au module 7 (mi-parcours) (β = - 0,43 ; p < 0,001 ; β = - 0,38 ; p = 0,005 et β = - 0,36 ; p = 0,007 respectivement). Le nombre de modules consultés, par ailleurs, était prédit significativement par le nombre de mots dans le 4 e module (β = 0,34 ; p < 0,001) et dans le 7 e module (β = 0,44 ; p < 0,001), ainsi que par le nombre d’entrées dans le journal du sommeil (β = 0,28 ; p < 0,001). Conclusion Les résultats ont confirmé qu’une plus grande interaction avec la plateforme influence positivement l’efficacité du traitement et qu’une utilisation accrue en début de traitement semble être un bon prédicteur de l’achèvement de celui-ci. Cette étude confirme l’importance de soutenir l’engagement des participants envers le traitement en ligne afin d’optimiser son efficacité. , Objectives Despite the existence of several online treatments for people with posttraumatic stress disorder (PTSD), few studies have examined usage data for such interventions. Given the potential of the online modality to alleviate barriers limiting access to psychological help, it is important to document users’ interactions with these tools in relation to the improvement of targeted symptoms. The objective of this study is to document usage data of the online treatment platform RESILIENT by people evacuated from the Fort McMurray, Alberta (Canada) fires, and to examine their association with the effectiveness of treatment on symptoms of posttraumatic stress disorder (PTSD), insomnia and depression, and adherence to treatment, as measured by the number of modules accessed by participants. Methods Ninety-seven people evacuated from the Fort McMurray fires with symptoms of PTSD, insomnia and depression were included in this study. Participants were invited to use the RESILIENT platform, an online therapist-assisted self-help treatment program that targets PTSD symptoms, sleep and mood, and includes 12 modules offering evidence-based cognitive-behavioural therapy (CBT) strategies. Both objective (e.g., number of modules accessed) and subjective (e.g., level of effort invested) usage data were collected. Results In order to predict the reduction in PTSD, depression and insomnia symptoms, as well as the number of modules accessed by participants, sequential regression models were conducted, with statistical control for pretreatment symptoms, age and gender. The final models revealed that a reduction in PTSD, depression and insomnia symptoms was significantly predicted by the number of modules accessed (β = -.41; -.53; -.49 respectively, all p <.001) as well as the mean self-reported level of effort at module 7 (midway) (β = -.43; p <.001; β = -.38; p = .005 and β = -.36; p = .007 respectively). The number of modules accessed, on the other hand, was significantly predicted by the number of words in the 4th module (β = .34; p <.001) and 7th module (β = .44; p <.001) and the number of sleep diary entries (β = .28; p <.001). Conclusion These results confirmed that increased interaction with the platform positively influences treatment effectiveness and that increased use at the beginning of treatment appears to be a good predictor of treatment completion. This study confirms the importance of sustaining participants’ commitment to online treatment in order to optimize its effectiveness.

Addressing the climate change adaptation puzzle: a psychological science perspective - Bechtoldt, Myriam N.; Götmann, Alexander; Moslener, Ulf; Pauw, W. Pieter (Climate Policy, 2021)

Lessons learned from the NSERC Canadian FloodNet on improving flood forecasting systems and management capacity - Xenopoulos, Marguerite; Coulibaly, Paulin; Anctil, Francois; Burn, Donald; Nguyen, Van-Thanh-Van (AGU Fall Meeting Abstracts, 2021)
In Canada, floods are the most common largely distributed hazard to life, property, the economy, water systems, and the environment costing the Canadian economy billions of dollars. Arising from this is FloodNet: a transdisciplinary strategic research network funded by Canadas Natural Sciences and Engineering Research Council, as a vehicle for a concerted nation-wide effort to improve flood forecasting and to better assess risk and manage the environmental and socio-economic consequences of floods. Four themes were explored in this network which include 1) Flood regimes in Canada; 2) Uncertainty of floods; 3) Development of a flood forecasting and early warning system and 4) Physical, socio-economic and environmental effects of floods. Over the years a range of statistical, hydrologic, modeling, and economic and psychometric analyses were used across the themes. FloodNet has made significant progress in: assessing spatial and temporal variation of extreme events; updating intensity-duration-frequency (IDF) curves; improving streamflow forecasting using novel techniques; development and testing of a Canadian adaptive flood forecasting and early warning system (CAFFEWS); a better understanding of flood impacts and risk. Despite these advancements FloodNet ends at a time when the World is still grappling with severe floods (e.g., Europe, China, Africa) and we report on several lessons learned. Mitigating the impact of flood hazards in Canada remains a challenging task due to the countrys varied geography, environment, and jurisdictional political boundaries. Canadian technical guide for developing IDF relations for infrastructure design in the climate change context has been recently updated. However, national guidelines for flood frequency analyses are needed since across the country there is not a unified approach to flood forecasting as each jurisdiction uses individual models and procedures. From the perspective of risk and vulnerability, there remains great need to better understand the direct and indirect impacts of floods on society, the economy and the environment.

Development of interactive diagnostic tools and metrics for the socio-economic consequences of floods - Parent, Annie-Claude; Fournier, Frédéric; Anctil, François; Morse, Brian; Baril-Boyer, Jean-Philippe; Marceau, Pascal (2021)
Spring floods have generated colossal damages to residential areas in the Province of Quebec, Canada, in 2017 and 2019. Government authorities need accurate modelling of the impact of theoretical floods in order to prioritize pre-disaster mitigation projects to reduce vulnerability. They also need accurate modelling of forecasted floods in order to direct emergency responses. We present a governmental-academic collaboration that aims at modelling flood impact for both theoretical and forecasted flooding events over all populated river reaches of meridional Quebec. The project, funded by the ministère de la Sécurité publique du Québec (Quebec ministry in charge of public security), consists in developing a diagnostic tool and methods to assess the risk and impacts of flooding. Tools under development are intended to be used primarily by policy makers. The project relies on water level data based on the hydrological regimes of nearly 25,000 km of rivers, on high-precision digital terrain models, and on a detailed database of building footprints and characterizations. It also relies on 24h and 48h forecasts of maximum flow for the subject rivers. The developed tools integrate large data sets and heterogeneous data sources and produce insightful metrics on the physical extent and costs of floods and on their impact on the population. The software also provides precise information about each building affected by rising water, including an estimated cost of the damages and impact on inhabitants.

Investigation of an Arctic hypertidal estuary under summer and winter conditions : cryo-hydrodynamic and hydrokinetic implications - Mohammadian, Abdolvahid (2021)
La modélisation numérique des estuaires hypertidaux intéresse particulièrement les ingénieurs impliqués dans la navigation maritime et le développement de projets d'énergie marémotrice. Au Québec (Canada), la majorité de ces estuaires à marée extrême sont situés dans des régions isolée de l'Arctique canadien et sont souvent des lieux de résidence des communautés autochtones du Nord canadien. La présente thèse vise à mieux comprendre les processus se manifestent dans ces environnements, avec une emphase particulière sur l'importance (1) de la forte dominance des marées, (2) de l'extrême variabilité bathymétrique et (3) de l'immense forçage climatique. La thèse tente de démontrer comment les modèles numériques peuvent être utilisés pour traiter ces particularités et peuvent être la meilleure méthode disponible pour étudier leurs effets dans des environnements éloignés peu étudies. Premièrement, dans le but d'évaluer le potentiel de courant de marée en eau libre (sans glace) de l'estuaire hypertidal de la rivière Koksoak (KRE), nous avons modélisé le débit de marée en utilisant un model numérique hydrodynamique réputé (Delft3D). Différents aspects de l'hydrodynamique côtière ont été étudiés grâce à la modélisation numérique 1D2D-3D. La variabilité spatio-temporelle de la densité de puissance hydrocinétique disponible a ensuite été quantifiée. Les résultats ont révélé l'énorme potentiel (1000 MW) d'énergie marémotrice présente à plusieurs endroits le long de l'estuaire, ce qui nécessite des études numériques plus approfondies. En mettant davantage l'accent sur la modélisation numérique du site, par exemple la publication d'un Atlas des courants de marée pour aider à la navigation maritime dans le KRE, nous avons constaté que certains problèmes de modélisation des estuaires n'étaient pas abordés. Compte tenu des conditions limites précises et des mesures in situ recueillies au cours de l'hiver 2017-2018, nous avons constaté que les meilleurs résultats pour l'étalonnage du modèle (niveau d'eau) en utilisant les paramètres/options disponibles conduisaient encore à certains ordres d'imprécision. sur les conditions aux limites de formse qualité (campagnes 2017-2018) qui ont effectivement amélioré les résultats numériques, nous avons constaté que les meilleurs résultats pour l'étalonnage du modèle (niveau d'eau) en utilisant les paramètres/options disponibles étaient encore associés à certains ordres d'imprécision. Par conséquent, l'objectif du deuxième travail était d'améliorer l'efficacité de la modélisation hydrodynamique pour les environnements de marée peu profonde. Nous avons introduit quelques hypothèses décrivant pourquoi les modèles de turbulence et de rugosité disponibles ne sont pas bien adaptés à la modélisation des estuaires avec de fortes variabilités spatiales et temporelles des profondeurs de marée. En conséquence (i) un modèle de turbulence k-ε étendu pour la paramétrisation adaptative de la viscosité turbulente en fonction de la profondeur, et une approche basée sur la direction de l'écoulement pour la paramétrisation de la rugosité du lit ont été développés, incorporés dans le modèle hydrodynamique employé (Delft3D). Le modèle modifié a montré une amélioration constante des prévisions du modèle dans les stations de champ proche et de champ lointain, par rapport aux schémas de paramétrage classiques. Enfin, un aspect manquant et mal compris des estuaires de latitude nordique est l'immense impact de l'hiver sur le flux des marées. Situé à la latitude 58°, le KRE subit l'effet intensif du climat arctique pendant la majeure partie de l'année, ce qui entraîne la formation de glace estuarienne rapide sur une grande partie de sa longueur. Plus précisément, et ce qui est le plus pertinent pour cette recherche, il est important de savoir comment le long hiver affecte les potentiels hydrocinétiques des estuaires des régions froides. Ainsi, la surfusion entraîne la formation de frasil et de glace de fond qui peuvent adhérer aux pales des turbines et provoquer leur dysfonctionnement. Dans les estuaires, la surfusion a une nature transitoire complexe car le point de congélation de l'eau salée est une fonction de la salinité et de la profondeur qui est changée par les marées au cours des cycles de marée. En raison du manque de données de terrain en hiver, nous avons collecté des paramètres hydrodynamiques en utilisant de nouvelles campagne de mesures en hiver 2018. Les observations ont montré que le risque de surfusion diminue à l'intérieur de l'estuaire, car en l'absence de débit fluvial, la salinité peut s'infiltrer beaucoup plus loin dans le fleuve. À l'intérieur, une modulation apparente de ∆T (la différence entre la température de l'eau et la température de congélation de l'eau), dépendant de la marée, a été observée avec une augmentation de la température pendant des marées montantes. Cette augmentation retarderait la surfusion, ce qui est un avantage majeur pour turbines. En réglant le module Delft3D-Ice, différents scénarios ont été définis pour l'étendue et l'épaisseur de la couvert de glace, et leurs réponses hydrodynamiques ont été analysées. Il a été démontré que la glace a des impacts complexes et non uniformes sur les caractéristiques hydrodynamiques de la KRE. Surtout, le débit des prismes de marée, qui est la principale source d'élan, peut être modifiée de manière démonstrative par la couverture de glace et la glace de marée plate. Les résultats suggèrent que les zones énergétiques sont légèrement affectées par la glace pendant la plus grande partie de l'hiver. Pendant l'hiver de pointe seulement, la glace pourrait considérablement diminuer densité moyenne de puissance des courants (par exemple, la puissance moyenne est égale ou supérieure à 7 kW m-2). Ces implications cryohydrodynamiques indiquent que l'hiver arctique n'est pas un obstacle à la production d'électricité dans le fleuve Koksoak, et l'énergie marémotrice serait un avantage annuel pour Kuujjuaq

Integrating Multiple Research Methods to Unravel the Complexity of Human‐Water Systems - Di Baldassarre, Giuliano; Cloke, Hannah; Lindersson, Sara; Mazzoleni, Maurizio; Mondino, Elena; Mård, Johanna; Odongo, Vincent; Raffetti, Elena; Ridolfi, Elena; Rusca, Maria; Savelli, Elisa; Tootoonchi, Faranak (AGU Advances, 2021)
Abstract Predicting floods and droughts is essential to inform the development of policy in water management, climate change adaptation and disaster risk reduction. Yet, hydrological predictions are highly uncertain, while the frequency, severity and spatial distribution of extreme events are further complicated by the increasing impact of human activities on the water cycle. In this commentary, we argue that four main aspects characterizing the complexity of human‐water systems should be explicitly addressed: feedbacks, scales, tradeoffs and inequalities. We propose the integration of multiple research methods as a way to cope with complexity and develop policy‐relevant science. , Plain Language Summary Several governments today claim to be following the science in addressing crises caused by the occurrence of extreme events, such as floods and droughts, or the emergence of global threats, such as climate change and COVID‐19. In this commentary, we show that there are no universal answers to apparently simple questions such as: Do levees reduce flood risk? Do reservoirs alleviate droughts? We argue that the best science we have consists of a plurality of legitimate interpretations and a range of foresights, which can be enriched by integrating multiple disciplines and research methods. , Key Points Accounting for both power relations and cognitive heuristics is key to unravel the interplay of floods, droughts and human societies Flood and drought predictions are complicated by the increasing impact of human activities on the water cycle We propose the integration of multiple research methods as a way to cope with uncertainty and develop policy‐relevant science

Le stress prénatal maternel et les problèmes comportementaux chez les enfants : effet modérateur de la consistance de la discipline - Daniel, Benjhyna (2021)
Le stress prénatal maternel (SPM) est un concept largement étudié et ce, autant par de méthodes objectives que subjectives. Certains chercheurs évaluent les symptômes d’anxiété et de dépression des femmes au cours de leur grossesse alors que d’autres préfèrent mesurer les niveaux de cortisol des femmes enceintes. Pour cette thèse, le SPM a été mesuré par deux méthodes différentes, soit l’exposition des femmes enceintes à une catastrophe naturelle et l’exposition des mêmes femmes enceintes à des événements de vie stressants plus courants. Puisqu’il est bien établi que ce type de stress engendre des répercussions négatives sur la femme enceinte ainsi que sur le développement de l’enfant, il est désormais d’intérêt d’accentuer les recherches sur les moyens qui permettent d’atténuer les conséquences d’un tel stress. Dans les études auprès des animaux, nous savons que les conditions de maternage ainsi que l'enrichissement environnemental semblent renverser les effets du SPM, mais nous ne savons pas si, chez les humains, un bon encadrement parental, c’est-à-dire un cadre structuré avec des règles prévisibles et consistantes, peut protéger les enfants des effets du SPM. L’objectif de cette thèse est donc d’augmenter notre compréhension sur l’effet protecteur de l’encadrement parental dans le développement d’enfants qui ont été exposés à différents types de SPM. Cet objectif pourra être atteint grâce à une collaboration internationale initiée par la Dre Suzanne King suite aux inondations qui se sont produites en 2008 dans l'état d'Iowa. Suite à la catastrophe, la Dre King est entrée en contact avec le Dr O’Hara afin d'évaluer la sévérité du stress dû aux inondations chez les femmes enceintes et pour déterminer les effets de ce stress sur leur enfant. Trois types de stress ont été évalués: le degré objectif de difficulté (p. ex., pertes financières), l'évaluation cognitive de la catastrophe en tant qu'expérience négative, neutre ou positive, et la détresse subjective causée par l'inondation (p. ex., symptômes de TSPT). Suite au recrutement des mères, les enfants de l'échantillon ont été évalués à l’âge de 2, 4, 5 et 7 ans. La présente thèse est composée de trois études. La première étude porte sur l’effet modérateur de l’encadrement parental sur les associations entre le SPM causé par les inondations d’Iowa et les problèmes comportementaux chez les enfants âgés de sept ans. Les résultats indiquent qu’un encadrement parental où la discipline est consistante protège les garçons qui ont été exposés au SPM objectif contre différents symptômes de problèmes internalisés et externalisés. La deuxième étude se penche également sur la question de l’effet protecteur de l’encadrement parental sur les associations entre le SPM et les problèmes comportementaux chez les enfants âgés de sept ans. Toutefois, cette étude s’est plutôt penchée sur l’influence du SPM lorsque celui-ci est causé par des événements de vie qui sont plus communs qu’un désastre naturel. De nouveau, les résultats de cette étude nous révèlent qu’un encadrement parental consistant joue le rôle de facteur de protection, chez les garçons qui ont été exposés au SPM causé par des événements de vie stressants, mais seulement en ce qui concerne les problèmes de comportement externalisés. La troisième étude vient reconsidérer l’effet protecteur de l’encadrement parental sur les liens entre le SPM et les problèmes comportementaux des enfants qui ont été exposés à un désastre naturel. Cependant, pour cette étude, les comportements des enfants n’ont pas été évalués par un questionnaire, mais plutôt par une méthode observationnelle (tâche de frustration). Toutefois, dans cette étude, il n’est ressorti aucun effet significatif de l’encadrement parental comme variable modératrice. En somme, nos résultats rapportent que l’implantation d’un cadre structuré et consistant peut venir pallier et même renverser les conséquences du SPM sur le comportement des garçons.

Quel regard porter sur le travail social à l’ère des changements climatiques? : le cas des inondations (2017-2019) au Québec - Hamelin, Marilou (2021)
Les changements climatiques anthropogéniques posent des défis énormes pour toutes les sociétés humaines. Ces défis majeurs mettront à l’épreuve les capacités d’adaptation des États et de ses institutions et des communautés partout dans le monde et devront se résoudre par un élan de solidarité humaine afin d’en atténuer les conséquences. Le Canada connaît déjà un réchauffement climatique important. Le pays a d’ailleurs récemment été touché par des événements climatiques extrêmes : des canicules, des feux de forêt, une sécheresse anormale et des inondations dont l’intensité est prévue d’augmenter avec les changements climatiques anthropogéniques. La province du Québec a quant à elle été touchée par de fortes inondations entre 2017 et 2019. L’objectif principal de la présente étude vise à discuter la manière dont le paradigme écosocial peut faire évoluer le travail social en tant que champ de savoir et d’intervention dans un contexte de changements climatiques. Cette étude s’est appuyée sur des données issues de groupes focus réalisés avec des intervenants suite aux inondations survenues au Québec (2017-2019). Notre analyse vise les interventions réalisées en contexte d’inondations, dans le sud de la province, mise en œuvre par le système de santé. Les données ont été collectées lors d’entrevues de groupe réalisées avec des intervenants psychosociaux et des gestionnaires de CI(U)SSS au courant des mois d’octobre et de novembre 2019. Les thèmes suivants ont émergé des analyses: les caractéristiques des inondations de 2019, les divergences d’opinions vis-à-vis des changements climatiques, l’aide et le soutien apportés durant les inondations et la participation citoyenne. J’insisterai également sur l’exacerbation possible des inégalités sociales dans ce contexte. D’autres thèmes se sont également révélés importants : l’engagement des intervenants psychosociaux, la participation et la décentralisation des décisions politiques. Enfin, mes réflexions porteront sur les conséquences sociales qu’entrainent les inondations et sur les types de pratiques sociales qui s’avèrent pertinentes à l’ère des changements climatiques et dans un contexte d’urgence.

Policies of Exclusion: The Case of Syrian Refugees in Lebanon - Kikano, Faten; Fauveaud, Gabriel; Lizarralde, Gonzalo (Journal of Refugee Studies, 2021)
Abstract When the Syrian war erupted in 2011, the Lebanese government withdrew from managing the influx of Syrian refugees. Three years later, Lebanon’s Council of Ministers set new regulations for Syrians with the purpose of reducing access to territory and persuading refugees to leave the country. This article analyses the reasons for and the outcomes of Lebanon’s response to the refugee crisis before and after 2014. It then examines, through a qualitative exploratory approach and based on two longitudinal case studies, the impact of Lebanese regulations. In both cases, the so-called ‘temporary gatherings’ became permanent settlements beyond the government’s control. The government’s strategy backfired: in attempting to avoid ghettos, it created them. We conclude that when refugee situations become protracted, most efforts aimed at excluding refugees fail. Excluding refugees increases their vulnerability and reduces their chances of repatriation or resettlement. To prevent this, we argue that hosting policies must lead to the temporary integration of refugees within urban systems and public institutions.
Keywords: Lizarralde_Gonzalo

Maladaptation, fragmentation, and other secondary effects of centralized post-disaster urban planning: The case of the 2011 “cascading” disaster in Japan - Kondo, Tamiyo; Lizarralde, Gonzalo (International Journal of Disaster Risk Reduction, 2021)
Keywords: Lizarralde_Gonzalo

Climate Change and Rainfall Intensity–Duration–Frequency Curves: Overview of Science and Guidelines for Adaptation - Martel, Jean-Luc; Brissette, François P.; Lucas-Picher, Philippe; Troin, Magali; Arsenault, Richard (Journal of Hydrologic Engineering, 2021)

The archaeology of climate change: The case for cultural diversity - Burke, Ariane; Peros, Matthew C.; Wren, Colin D.; Pausata, Francesco S. R.; Riel-Salvatore, Julien; Moine, Olivier; De Vernal, Anne; Kageyama, Masa; Boisard, Solène (Proceedings of the National Academy of Sciences, 2021)
Anthropogenic climate change is currently driving environmental transformation on a scale and at a pace that exceeds historical records. This represents an undeniably serious challenge to existing social, political, and economic systems. Humans have successfully faced similar challenges in the past, however. The archaeological record and Earth archives offer rare opportunities to observe the complex interaction between environmental and human systems under different climate regimes and at different spatial and temporal scales. The archaeology of climate change offers opportunities to identify the factors that promoted human resilience in the past and apply the knowledge gained to the present, contributing a much-needed, long-term perspective to climate research. One of the strengths of the archaeological record is the cultural diversity it encompasses, which offers alternatives to the solutions proposed from within the Western agro-industrial complex, which might not be viable cross-culturally. While contemporary climate discourse focuses on the importance of biodiversity, we highlight the importance of cultural diversity as a source of resilience.

Flood Risk Assessment under Climate Change: The Petite Nation River Watershed - Oubennaceur, Khalid; Chokmani, Karem; Gauthier, Yves; Ratte-Fortin, Claudie; Homayouni, Saeid; Toussaint, Jean-Patrick (Climate, 2021)
In Canada, climate change is expected to increase the extreme precipitation events by magnitude and frequency, leading to more intense and frequent river flooding. In this study, we attempt to map the flood hazard and damage under projected climate scenarios (2050 and 2080). The study was performed in the two most populated municipalities of the Petite Nation River Watershed, located in southern Quebec (Canada). The methodology follows a modelling approach, in which climate projections are derived from the Hydroclimatic Atlas of Southern Quebec following two representative concentration pathways (RCPs) scenarios, i.e., RCP 4.5 and RCP 8.5. These projections are used to predict future river flows. A frequency analysis was carried out with historical data of the peak flow (period 1969–2018) to derive different return periods (2, 20, and 100 years), which were then fed into the GARI tool (Gestion et Analyse du Risque d’Inondation). This tool is used to simulate flood hazard maps and to quantify future flood risk changes. Projected flood hazard (extent and depth) and damage maps were produced for the two municipalities under current and for future scenarios. The results indicate that the flood frequencies are expected to show a minor decrease in peak flows in the basin at the time horizons, 2050 and 2080. In addition, the depth and inundation areas will not significantly change for two time horizons, but instead show a minor decrease. Similarly, the projected flood damage changes in monetary losses are projected to decrease in the future. The results of this study allow one to identify present and future flood hazards and vulnerabilities, and should help decision-makers and the public to better understand the significance of climate change on flood risk in the Petite Nation River watershed.
Keywords: Site_internet_RIISQ

Poorly adapted but nothing to lose? A study on the flood risk – income relationship with a focus on low-income households - Osberghaus, Daniel (Climate Risk Management, 2021)
Abstract Flood risk may differ across income levels. In this paper, I employ unique survey data from more than 8000 households in Germany to derive an integrated flood risk indicator that accounts for local flood exposure, assets-at-risk, housing characteristics, and household coping behavior. The results suggest that low-income households, due to their smaller homes and less valuable assets, face lower monetary flood risks than wealthier households despite the former’s limited capacity to implement protection measures and purchase insurance. Relative to the available financial budget, however, expected flood damage weighs higher for low-income households.
MAG ID: 3119722510

2 °C vs. High Warming: Transitions to Flood-Generating Mechanisms across Canada - Teufel, Bernardo; Sushama, Laxmi (Water, 2021)
Fluvial flooding in Canada is often snowmelt-driven, thus occurs mostly in spring, and has caused billions of dollars in damage in the past decade alone. In a warmer climate, increasing rainfall and changing snowmelt rates could lead to significant shifts in flood-generating mechanisms. Here, projected changes to flood-generating mechanisms in terms of the relative contribution of snowmelt and rainfall are assessed across Canada, based on an ensemble of transient climate change simulations performed using a state-of-the-art regional climate model. Changes to flood-generating mechanisms are assessed for both a late 21st century, high warming (i.e., Representative Concentration Pathway 8.5) scenario, and in a 2 °C global warming context. Under 2 °C of global warming, the relative contribution of snowmelt and rainfall to streamflow peaks is projected to remain close to that of the current climate, despite slightly increased rainfall contribution. In contrast, a high warming scenario leads to widespread increases in rainfall contribution and the emergence of hotspots of change in currently snowmelt-dominated regions across Canada. In addition, several regions in southern Canada would be projected to become rainfall dominated. These contrasting projections highlight the importance of climate change mitigation, as remaining below the 2 °C global warming threshold can avoid large changes over most regions, implying a low likelihood that expensive flood adaptation measures would be necessary.

Assessment of non-stationary IDF curves under a changing climate: Case study of different climatic zones in Canada - Silva, Daniele Feitoza; Simonovic, Slobodan P.; Schardong, Andre; Joel Avruch Goldenfum; Goldenfum, Joel Avruch (Journal of Hydrology: Regional Studies, 2021)
Abstract Study region Canada. Study focus Given the effects of climate change on extreme precipitation, updated Intensity-Duration-Frequency (IDF) relationships have been adopted across Canada. Since the IDFs’ generation is based on the assumption of stationarity, the rainfall statistics information may be unreliable. Recent research is attempting to develop a new methodology to integrate non-stationarity and climate change into IDFs updating process. Up to now, there is no comprehensive evaluation of the IDFs updating procedure at different locations. In this study, we analyzed the combined effect of non-stationarity and climate change on future IDFs at six selected gauging stations across Canada. New hydrological insights for the region A comparison of the updated future IDFs with historical IDFs indicates an intensification of extreme events for all study areas, increasing hazard to them. Sites located in the Northeast coastal region will be the most affected in the future by the extreme precipitation. In addition, there is a clear indication that rare events (100-year return period) will become more frequent (in some cases increase up to 443 % of the water infrastructure risk of failure has been observed). We argue that the above findings (i) offer a new overview of future extreme precipitation across Canada, and (ii) should be considered by the stakeholders with respect to climate change adaptation decisions.
MAG ID: 3188856126

Changes in floodplain regimes over Canada due to climate change impacts: Observations from CMIP6 models - Mohanty, Mohit Prakash; Simonovic, Slobodan P. (Science of The Total Environment, 2021)
Abstract With the recent Coupled Model Intercomparison Project Phase 6 (CMIP6), water experts and flood modellers are curious to explore the efficacy of the new and upgraded climate models in representing flood inundation dynamics and how they will be impacted in the future by climate change. In this study, for the first time, we consider the latest group of General Circulation Models (GCMs) from CMIP6 to examine the probable changes in floodplain regimes over Canada. A set of 17 GCMs from Shared Socioeconomic Pathways (SSPs) 4.5 (medium forcing) and 8.5 (high end forcing) common to historical (1980 to 2019), near-future (2021 to 2060), and far-future (2061 to 2100) time-periods are selected. A comprehensive framework consisting of hydrodynamic flood modelling, and statistical experiments are put forward to derive high-resolution Canada-wide floodplain maps for 100 and 200-yr return periods. The changes in floodplain regimes for the future periods are analyzed over drainage basin scale in terms of (i) changes in flood inundation extents, (ii) changes in flood hazards (high and very-high classes), and (iii) changes in flood frequency. Our results show a significant rise (>30%) in flood inundation extents in the future periods; particularly intense over western and eastern regions. The flood hazards are expected to cover ~16% more geographical area of Canada. We also find that large areas in northern and western Canada and a few spots in the eastern parts of Canada will be getting flooded more frequently compared to the historical period. The observations derived from this study are vital for enhancing flood preparedness, optimal land-use planning, and refurbishing both structural and non-structural flood control options for improved resilience. The study instills new knowledge on revamping the existing flood management approaches and adaptation strategies for future protection.
MAG ID: 3166747757

Fiscal Decentralization and Natural Disaster Mitigation: Evidence from the United States - Miao, Qing; Shi, Yu; Davlasheridze, Meri (Public Budgeting & Finance, 2021)
How decentralized government structure influences public service delivery has been a major focus of debate in the public finance literature. In this paper, we empirically examine the effect of fiscal decentralization on natural disaster damages across the U.S. states. We construct a unique measure of decentralization using state and local government expenditures on natural resources, which include investment in flood control and mitigation measures, among others. Using state‐level panel data from 1982 to 2011, we find that states that are more decentralized in natural resource expenditures have experienced more economic losses from floods and storms. This effect is only pronounced in states that are at higher risks of flooding. Our findings suggest that fiscal decentralization may lead to inefficient protection against natural disasters and provide implications for the assignment of disaster management responsibilities across different levels of government in the U.S. federal system.
MAG ID: 3091940386

The disaster trap: Cyclones, tourism, colonial legacies, and the systemic feedbacks exacerbating disaster risk - Lazarus, Eli D. (Transactions of the Institute of British Geographers, 2021)
The long, open-ended period of recovery from a disaster event is the phase of a disaster that the interdisciplinary field of disaster studies struggles to understand. In the process of rebuilding, places do not simply reset – they transform, often in ways that confound any reduction of disaster risk, instead making people and settings more vulnerable to future hazard events. Reducing disaster risk is regarded as a global priority, but policies intended to reduce disaster risk have been largely ineffective. This obduracy represents a grand challenge in disaster studies. Here, I propose that the correlated trends of runaway economic costs of disaster events, growing social inequity, environmental degradation, and resistance to policy intervention in disaster settings are hallmark indicators of a system trap – a dynamic in which self-reinforcing feedbacks drive a system toward an undesirable and seemingly inescapable state, with negative consequences that tend to amplify each other over time. I offer that these trends in disaster settings are the collective expression of an especially powerful and distinct kind of system trap, which here I term the “disaster trap” – a new theoretical concept to help explain and address runaway disaster risk. I suggest that disaster traps are likely strongest in tourism-dominated coastal settings with high exposure to tropical cyclones and colonial histories of racial capitalism, which I explore with an empirical illustration from Antigua & Barbuda. Formalising a linkage between gilded and safe-development traps matters because their effects likely compound each other nonlinearly, such that disaster risk only increases and disaster risk reduction becomes increasingly difficult to achieve. Addressing traps requires understanding them as dynamic systems, described as fundamentally and completely as possible – their components, mechanisms, drivers, and structure – in order to reveal when and where interventions might be most effective at reducing disaster risk.
MAG ID: 3216773480

Justice and Resilience in Flood Risk Management: What Are the Socio-Political Implications? - Thaler, Thomas (2021)
Flood risk management requires to comprehensively assess how policy strategies may affect individuals and communities. However, policy development and implementation often downplay or even increase social inequality. Analysis of the social and societal implications of strategies and implementation projects to manage flood hazards is still in its infancy. To close this gap, this chapter critically questions the roles of social justice and their political implications for flood risk management with regard to resilience. The chapter discusses and argues how different theoretical concepts as well as different perspectives on justice (e.g. social, environmental and climate justice) and resilience in flood risk management are related. There is a strong need to have a broader and more in-depth discussion about the role of justice in the current resilience debate. Finally, the chapter presents the outline of a future research agenda.
MAG ID: 3185363811

Cascading disasters : Multiple risk reduction and resilience - Alexander, D. (Handbook of Disaster Risk Reduction for Resilience, 2021)
Keywords: Ouvrage_Collectif_Numéro1

Scenarios of Human Responses to Unprecedented Social‐Environmental Extreme Events - Rusca, Maria; Messori, Gabriele; Di Baldassarre, Giuliano (Earth's Future, 2021)
Abstract In a rapidly changing world, what is today an unprecedented extreme may soon become the norm. As a result, extreme‐related disasters are expected to become more frequent and intense. This will have widespread socio‐economic consequences and affect the ability of different societal groups to recover from and adapt to rapidly changing environmental conditions. Therefore, there is the need to decipher the relation between genesis of unprecedented events, accumulation and distribution of risk, and recovery trajectories across different societal groups. Here, we develop an analytical approach to unravel the complexity of future extremes and multiscalar societal responses—from households to national governments and from immediate impacts to longer term recovery. This requires creating new forms of knowledge that integrate analyses of the past—that is, structural causes and political processes of risk accumulation and differentiated recovery trajectories—with plausible scenarios of future environmental extremes grounded in the event‐specific literature. We specifically seek to combine the physical characteristics of the extremes with examinations of how culture, politics, power, and policy visions shape societal responses to unprecedented events, and interpret the events as social‐environmental extremes. This new approach, at the nexus between social and natural sciences, has the concrete advantage of providing an impact‐focused vision of future social‐environmental risks, beyond what is achievable within conventional disciplinary boundaries. In this paper, we focus on extreme flooding events and the societal responses they elicit. However, our approach is flexible and applicable to a wide range of extreme events. We see it as the first building block of a new field of research, allowing for novel and integrated theoretical explanations and forecasting of social‐environmental extremes. , Key Points We conceptualize unprecedented extremes as social‐environmental processes shaped by institutional, political, and economic change As social‐environmental extremes become more frequent, there is an urgency to unravel their genesis and the possible societal responses This approach is the first building block of a new field of research in social‐environmental extreme event forecasts , Plain Language Summary The world is seeing increases in a range of extreme events, and this increase may continue or even accelerate in the future, due to anthropogenic climate change. Furthermore, it is often those who are already vulnerable that experience the biggest impacts from these extremes. Yet, there is little understanding of the possible societal responses to unprecedented events. This underscores the urgency of creating innovative approaches to develop plausible scenarios of societal responses and, in turn, mitigate hazards and reduce vulnerability and exposure to extreme events. In this commentary, we develop a truly interdisciplinary conceptual approach to better understand how different societal groups might interact with and respond to future unprecedented extreme events. We combine social science theories describing how different societal groups are affected by, and recover from, extreme events with projections from the literature identifying plausible areas at risk of unprecedented occurrences and local analyses of past extreme events. We see this as the first building block of a new field of research in forecasting social‐environmental extremes that could support governments, civil protection agencies, and civil society organizations to ensure a fairer, improved response to future events.

Modeling the Impacts of Urban Flood Risk Management on Social Inequality - Moulds, Simon; Buytaert, Wouter; Templeton, Michael R.; Kanu, Ishmael (Water Resources Research, 2021)
Abstract The exposure of urban populations to flooding is highly heterogeneous, with the negative impacts of flooding experienced disproportionately by the poor. In developing countries experiencing rapid urbanization and population growth a key distinction in the urban landscape is between planned development and unplanned, informal development, which often occurs on marginal, flood‐prone land. Flood risk management in the context of informality is challenging, and may exacerbate existing social inequalities and entrench poverty. Here, we adapt an existing socio‐hydrological model of human‐flood interactions to account for a stratified urban society consisting of planned and informal settlements. In the first instance, we use the model to construct four system archetypes based on idealized scenarios of risk reduction and disaster recovery. We then perform a sensitivity analysis to examine the relative importance of the differential values of vulnerability, risk‐aversion, and flood awareness in determining the relationship between flood risk management and social inequality. The model results suggest that reducing the vulnerability of informal communities to flooding plays an important role in reducing social inequality and enabling sustainable economic growth, even when the exposure to the flood hazard remains high. Conversely, our model shows that increasing risk aversion may accelerate the decline of informal communities by suppressing economic growth. On this basis, we argue for urban flood risk management which is rooted in pro‐poor urban governance and planning agendas which recognize the legitimacy and permanence of informal communities in cities. , Key Points The distribution of flood risk in urban areas is uneven, with the negative impacts experienced disproportionately by the urban poor Our model shows that reducing the vulnerability of informal residents to flooding can reduce inequality, even when their exposure is high Based on the model results, we argue that urban flood risk management should be rooted in pro‐poor urban governance and planning agendas

Flooded Social Connections - Ratnadiwakara, Dimuthu (The Quarterly Journal of Finance, 2021)
Does salient information on social media influence individuals’ economic decisions and beliefs? Using aggregated data from Facebook and a difference-in-differences strategy, I show that individuals who are socially connected to someone affected by Hurricane Harvey are more likely to purchase flood insurance policies after the event. This effect is stronger in areas at higher risk of flooding. Being socially connected to someone affected by Hurricane Harvey also influences individuals’ perceptions of global warming.

Gouvernance régionale et stratégies d’adaptation aux inondations en contexte de changements climatiques : une étude de cas, la MRC de Vaudreuil-Soulanges - Thivierge, Caroline (2021)
L’objectif de cette recherche est d’identifier les stratégies d’adaptation qui sont requises et du ressort d’une municipalité régionale de comté face aux inondations. Le réchauffement global des températures soulève plusieurs inquiétudes quant à la modification du cycle hydrologique. Les inondations figurent en tête de liste des enjeux de sécurité civile des municipalités riveraines. Au Québec, on prévoit une augmentation des précipitations printanières, automnales et hivernales, ainsi que des débits hivernaux plus élevés et un devancement des crues printanières. Des projections qui peuvent influencer l’approche de gestion des barrages, bien que le contrôle des niveaux d’eau ne soit pas une panacée vis-à-vis des inondations. Il suppose une gestion intégrée de l’eau parfois complexe. Aussi, les administrations locales ne siègent pas toujours aux comités responsables de la régularisation des cours d’eau. Celles-ci se retrouvent sur la ligne de front sans pour autant avoir le pouvoir et les ressources financières pour y faire face. Les crues exceptionnelles de 2017 et 2019 ont conduit la Municipalité régionale de comté de Vaudreuil-Soulanges à mettre à jour ses plans d’urgence et à mettre en place une cellule de crise. Elle applique une stratégie d’adaptation correspondant aux 4 axes du Plan de protection du territoire face aux inondations du ministère des Affaires municipales et de l’Habitation. Ces outils enrichissent leur capacité d’adaptation par l’acquisition de nouvelles connaissances et d’une nouvelle cartographie des zones inondables. Les vulnérabilités qui résultent de contraintes liées à l’aménagement du territoire, ainsi que d’enjeux réglementaires posent un défi pour le développement du territoire et la relocalisation de résidences inondées. Il convient de sonder la population sur sa vision de la résilience afin d’assurer une meilleure acceptabilité sociale des décisions à venir. Une vulnérabilité importante réside dans les écarts de perception du risque entre les municipalités et entre les individus ; ce qui engendre des enjeux de sécurité, de communication et de gouvernance. Les instances locales peuvent miser sur leurs habiletés de mobilisation pour réunir la communauté autour du développement d’un plan d’adaptation aux changements climatiques et ainsi harmoniser les perceptions. Finalement, l’épuisement des ressources humaines des municipalités inondées à répétition est à considérer. Il appert qu’il est essentiel d’identifier et de mettre en place les outils et ressources pour les soutenir.
Keywords: Ouvrage_Collectif_Numéro1

Improving flood resilience through governance strategies: Gauging the state of the art - Matczak, Piotr; Hegger, Dries (WIREs Water, 2021)
Abstract There has been an upsurge in studies of flood risk governance (FRG): steering and decision‐making by public and private actors as a complement to risk assessments and technical management options. The scholarly debate is, however, highly fragmented, complicating the production of cumulative insights. To address this knowledge gap, we used six governance strategies for achieving flood resilience that previously have been put forward as a conceptual framework to review 121 articles published between 2016 and 2019, complemented with insights contained in recent overview articles, to gauge the state‐of‐the‐art in FRG literature: to (a) diversify flood risk management strategies; (b) align the strategies; (c) adequately involve private actors, including citizens; (d) put an adequate rule system in place; (e) cater for sufficient monetary and non‐monetary resources; (f) inspire an open and inclusive normative debate. We found, first, that literature is producing insights on increasingly technically advanced risk assessments and agent‐based models but societal debate on justice in flood risk governance is getting attention. A clearly emerging topic is that of citizen engagement in flood risk governance. Second, the geographical focus of the studies is still skewed toward the Global North. To make progress in understanding flood risk governance for better resilience more systematic and comparative empirical assessments of flood risk governance in order to derive generalizable lessons while better taking into account the context‐specificity of FRG. Testing flood risk governance solutions against comparative cases, by balancing the geographical scope of research efforts, and enhancing interdisciplinary and transdisciplinary working is a way to deliver knowledge for more resilience. This article is categorized under: Human Water > Water Governance Engineering Water > Planning Water
Keywords: Ouvrage_Collectif_Numéro1

Flood exposure and social vulnerability in the United States - Tate, Eric; Rahman, Asif; Emrich, Christopher T.; Sampson, Christopher C. (Natural Hazards, 2021)
Human exposure to floods continues to increase, driven by changes in hydrology and land use. Adverse impacts amplify for socially vulnerable populations, who disproportionately inhabit flood-prone areas. This study explores the geography of flood exposure and social vulnerability in the conterminous United States based on spatial analysis of fluvial and pluvial flood extent, land cover, and social vulnerability. Using bivariate Local Indicators of Spatial Association, we map hotspots where high flood exposure and high social vulnerability converge and identify dominant indicators of social vulnerability within these places. The hotspots, home to approximately 19 million people, occur predominantly in rural areas and across the US South. Mobile homes and racial minorities are most overrepresented in hotspots compared to elsewhere. The results identify priority locations where interventions can mitigate both physical and social aspects of flood vulnerability. The variables that most distinguish the clusters are used to develop an indicator set of social vulnerability to flood exposure. Understanding who is most exposed to floods and where, can be used to tailor mitigation strategies to target those most in need.
MAG ID: 3119415889

Spatiotemporal Variations in Meteorological Disasters and Vulnerability in China During 2001–2020 - Li, Ying; Zhao, Shanshan; Zhao, Shiqiang; Wang, Guojie (Frontiers in Earth Science, 2021)
Based on the Yearbook of Meteorological Disasters in China, we analyzed the spatiotemporal variations in major meteorological disaster (MD) losses at the provincial scale during 2001–2020 to determine the spatiotemporal variations in MDs and vulnerability in China. Our results suggest that the impacts of MDs, including floods, droughts, hail and strong winds (HSs), low temperature and frosts (LTFs), and typhoons, have been substantial in China. MDs in China affect an average of 316.3 million people and 34.3 million hectares of crops each year, causing 1,739 deaths and costing 372.3 billion yuan in direct economic losses (DELs). Floods and droughts affected more of the population in China than the other MDs. Fatalities and DELs were mainly caused by floods, and the affected crop area was mainly impacted by drought. The national average MD losses decreased significantly, except for DELs. The trends in the affected population and crop area were mainly caused by droughts, and the trends in fatalities and DELs were dominated by floods. Floods and typhoons showed increasing influence in the last two decades relative to other disasters. The annual mean and long-term trends in MD losses exhibited regional heterogeneity and were subject to different dominant hazards in different regions. The disaster losses and their trends in southeastern China were mainly attributed to typhoons. The affected population, crop area, and DELs were all significantly and positively correlated with exposure. The vulnerability of the population, crops, and economy tended to decrease. Economic development reduced the vulnerability of the population and economy but showed no significant influence on the vulnerability of crops. Our findings suggest that more focus should be placed on the impacts of floods and typhoons and that socioeconomic development has an important influence on the vulnerability of the population and economy. These results provide a foundation for designing effective disaster prevention and mitigation measures.
MAG ID: 4200618679

Vulnérabilités psychosociales des populations rurales du Québec en temps de pandémie - Lessard, Lily; Simard, Dominic; Morin, Marie-Hélène (Santé Publique, 2021)
Keywords: Lessard_Lily

Impact of climate change on the vulnerability of drinking water intakes in a northern region - Leveque, B.; Burnet, J.-B.; Dorner, S.; Bichai, F. (Sustainable Cities and Society, 2021)
Keywords: Dorner_Sarah

Leveraging Hazard, Exposure, and Social Vulnerability Data to Assess Flood Risk to Indigenous Communities in Canada - Chakraborty, Liton; Thistlethwaite, Jason; Minano, Andrea; Henstra, Daniel; Scott, Daniel (International Journal of Disaster Risk Science, 2021)
Abstract This study integrates novel data on 100-year flood hazard extents, exposure of residential properties, and place-based social vulnerability to comprehensively assess and compare flood risk between Indigenous communities living on 985 reserve lands and other Canadian communities across 3701 census subdivisions. National-scale exposure of residential properties to fluvial, pluvial, and coastal flooding was estimated at the 100-year return period. A social vulnerability index (SVI) was developed and included 49 variables from the national census that represent demographic, social, economic, cultural, and infrastructure/community indicators of vulnerability. Geographic information system-based bivariate choropleth mapping of the composite SVI scores and of flood exposure of residential properties and population was completed to assess the spatial variation of flood risk. We found that about 81% of the 985 Indigenous land reserves had some flood exposure that impacted either population or residential properties. Our analysis indicates that residential property-level flood exposure is similar between non-Indigenous and Indigenous communities, but socioeconomic vulnerability is higher on reserve lands, which confirms that the overall risk of Indigenous communities is higher. Findings suggest the need for more local verification of flood risk in Indigenous communities to address uncertainty in national scale analysis.

Environmental vulnerability and resilience: Social differentiation in short‐ and long‐term flood impacts - Houston, Donald; Werritty, Alan; Ball, Tom; Black, Andrew (Transactions of the Institute of British Geographers, 2021)
This paper finds that social differentiation in flood impacts is relatively small soon after a flood, with some surprising results such as professionals and homeowners badly affected in the short‐term – but widens over time, with socially disadvantaged groups displaying less recovery. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts. , This paper reports household questionnaire survey results on vulnerability and resilience to flooding from one of the largest and most representative samples ( n = 593) of households up to 12 years after they were flooded, and is one of the first to provide detailed analysis of social differentiation in long‐term flood impacts. A novel finding is that social differentiation in flood impacts is relatively small soon after a flood, but widens over time, with socially disadvantaged groups displaying less recovery. The patterns of social differentiation in vulnerability and resilience to flooding differ markedly according to the type and timescale of the impact, with some normally socially advantaged groups (e.g., professionals and homeowners) being most vulnerable to short‐term impacts. Consistent with some existing studies, we found that older residents (age 70+) have greater resilience to flood impacts, although our sample may not capture the frailest individuals. As in previous research, low income is linked to lower resilience, particularly in the long term. We find that prior experience of flooding, despite enhancing preparedness, overall erodes rather than enhances resilience to flooding. Flood warnings are effective at reducing vulnerability to short‐term impacts. Underlying influences on resilience to natural disasters are complex and may only be revealed by multivariate analysis and not always be evident in simple observed patterns. The paper concludes that vulnerability and resilience to flooding are sensitive to financial resources, institutional support (chiefly from a landlord), and capacity to deal with disruption (chiefly time availability, which is low among professionals and high among retired people). An implication of these findings is that existing indices of flood vulnerability that use multiple measures of social deprivation should be used with caution, as not all conventional aspects of social deprivation are necessarily associated with greater vulnerability to flood impacts.

Improving GALDIT-based groundwater vulnerability predictive mapping using coupled resampling algorithms and machine learning models - Barzegar, Rahim; Razzagh, Siamak; Quilty, John; Adamowski, Jan; Kheyrollah Pour, Homa; Booij, Martijn J. (Journal of Hydrology, 2021)